Modelling of regional higher education services market: microeconomics methodologіcal approach - Сухий, Олег Орестович (Technology audit and production reserves, 2014)
This article presents the analysis of changes in education services market in recent years, when total number of freshmen decreased rapidly, that caused significant fall of income of many colleges and universities. Under such circumstances total revenues are proposed to be considered as a key parameter for maximizing from financial point of view in order to reach financial stability of colleges and universities. The model of kinked demand curve is applied to present situation of higher education services market in Ukraine. Instead of traditional for Ukraine accountant approach to calculation of tuition cost, calculation of changes in demand and total revenue are carried out on the basis of price elasticity of demand for higher education services. Relative index of price adjustment effectiveness is suggested to valuate impact of tuition changes on total revenues. Proposed models, analytical instruments and recommendations could help colleges and universities to maintain market share and their income base by means of scientifically based pricing strategy.